Analysis Of Knowledge Management Maturity Level Based On ISO 30401 And Quality Management System To Reduce The Number Customer Complaints - Safira, Nadya; Andhika, Rully (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
This research is carried out by the phenomenon of the increase in the number of customer complaints in the last four years at PT XX, which operates in the field of supplier of products and services in the construction sector. From the results of further research, it was found that there were problems in implementing KM. For this reason, this research aims to measure the Knowledge Management Maturity Level based on ISO 30401 and the quality management system as a strategy for facing global competitive conditions in the future so that leaders can develop effective strategies to reduce loss of organizational knowledge and customer complaints that occur due to lack of knowledge management. This research aims to obtain tools to measure knowledge management maturity in the company that supplies products and services in the construction sector so that management can develop strategies to reduce customer complaints. In several previous studies, knowledge management maturity levels were usually measured in contractor companies to prevent construction failures, but this research was carried out on the company that supplies products and services to contractors. The research methods used include literature studies, expert validation, and questionnaires. The results of this research are ten research sub-variables with 41 indicators as the tools for assessing the knowledge management maturity level. When tested at PT XX, it showed that the knowledge maturity is at level 4, where the organization has managed knowledge well and can be said to be mature. This result is already validated by experts who work in that company.